The effects of supercritical CO2 on the seepage characteristics and microstructure of water-bearing bituminous coal at in-situ stress conditions - Li, Chengtian; Zheng, Jingwei; Huang, Saipeng (Frontiers in Earth Science, 2023)
CO2 geological storage (CGS) is considered to be an important technology for achieving carbon peak and carbon neutralization goals. Injecting CO2 into deep unminable coal seams can achieve both CGS and enhance coalbed methane (ECBM) production. Therefore, the deep unminable coal seams are considered as promising geological reservoirs. CO2 exists in a supercritical CO2 (ScCO2) when it was injected into deep unminable coal seams. The injection of ScCO2 can induce changes in the seepage characteristics and microstructure of deep water-bearing coal seams. In this study, typical bituminous coal from Shenmu, Shanxi Province was used to investigate the effects of ScCO2 on seepage characteristics, pore characteristics, and mineral composition through experiments such as seepage tests, low-temperature liquid nitrogen adsorption, and X-ray diffraction (XRD). The results indicate that ScCO2 treatment of dry and saturated coal samples caused a significant increase in clay mineral content due to the dissolution of carbonates, leading to the conversion of adsorption pores to seepage pores and an improvement in seepage pore connectivity. Therefore, the Brunauer-Emmett-Teller (BET) specific surface area and pore volume of the two coal samples both decreased after ScCO2 treatment. Moreover, the permeability of dry and saturated coal samples increased by 191.53% and 231.71% at 10 MPa effective stress respectively. In semi-saturated coal samples, a large amount of dolomite dissolved, leading to the precipitation of Ca2+ and CO32- to form calcite. This caused pore throats to clog and macropores to divide. The results show that the pore volume and average pore size of coal samples decrease, while the specific surface area increases after ScCO2 treatment, providing more space for gas adsorption. However, the pore changes also reduced the permeability of the coal samples by 32.21% and 7.72% at effective stresses of 3 MPa and 10 MPa, respectively. The results enhance our understanding of carbon sequestration through ScCO2 injection into water-bearing bituminous coal seams.